Unusual paraneoplastic syndrome of inappropriate antidiuretic hormone secretion with gastric cancer - Pai, Ananth; Pervin, Saniya (International Journal of Research in Medical Sciences, 2019)
Syndrome of inappropriate antidiuretic hormone secretion (SIADH) results in impaired water excretion and consequent water intoxication and hyponatremia. In patients with cancer, SIADH is most commonly driven by ectopic ADH production, a paraneoplastic syndrome frequently seen in small cell lung cancer. A 63 year old male presented with loss of appetite, vomiting and hiccups. No abnormalities were detected on physical examination. Upper gastrointestinal endoscopy showed a proliferative growth in the stomach and histopathology report confirmed gastric adenocarcinoma. His laboratory investigations revealed low serum sodium and further work up for SIADH confirmed the diagnosis. The patient was treated with hypertonic saline and he improved symptomatically. He was subsequently treated with two cycles of capecitabine and oxaliplatin. The patient was asymptomatic and maintained a serum sodium in the range of 120 to 130 mEq/L, with a serum sodium of 127 mEq/L on follow up.